Psychological Distress in Diabetic and Myocardial Infarction Patients in Erbil City- Comparative Study - Mosleh Saber Kareem; Muhammad Hasan Awla; Dlzar Sadeeq Anwar; Iman Saleh Azeez; Sideeq Sadir Ali (Hawler Medical University, 2023)
ABSTRACT Background and Objectives: Psychological distress refers to a range of negative emotional experiences, such as anxiety, depression, and stress. Diabetes mellitus and myocardial infarction, are two medical conditions that can have a significant impact on an individual's psychological well-being. Therefore, in this study, we aimed to assess and compare psychological distress among diabetes mellitus (DM) and myocardial infarction (MI) patients in Erbil City. Methods: Quantitative, comparative study design was conducted on 100 patients 50 of them were diabetes mellitus patients in Layla Qasm Center and the other 50 were myocardial infarction patients at Cardiac Centre in Erbil City. The study was conducted from 12h April 2023 till 20th June 2023 and the data was collected from 20 h April 2022 till 24th May 2023. Results: The result showed that the majority of myocardial infarction patients were old adults which is (42%) between 57-68 years, married, illiterate and lived in urban. On the other hand, the majority of diabetes mellitus patients were middle-aged adults which are (42%) between 45-56 years, married illiterate and lived in urban. The ranges of the genders are equal which (50%) are male and (50%) being female. Also, most myocardial infarction patients are non-smokers (52%), and (34%) are smokers. In contrast, the majority of diabetes mellitus patients are (40%) non-smokers, and (20%) are smokers. Conclusions: psychological distress can negatively affect individuals who face chronic conditions such as myocardial infarction and diabetes mellitus.